2017
DOI: 10.1111/1759-7714.12546
|View full text |Cite
|
Sign up to set email alerts
|

UNBS5162 inhibits the proliferation of human A549 non‐small‐cell lung cancer cells by promoting apoptosis

Abstract: BackgroundLung cancer is one of the most frequently diagnosed malignancies in the world, thus developing novel anticancer reagents for lung cancer treatment is critical.MethodsWe performed cell counting kit‐8 and cell colony formation assays to investigate the role of UNBS5162 in the proliferation of A549 cells. Invasion and migration assays were applied to study the inhibitory effect of UNBS5162 on non‐small cell lung cancer cells. To detect the effect of UNBS5162 on A549 cell apoptosis, Annexin‐V fluorescein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Shukla et al (26) reported a number of applications of apoptosis in prostate cancer. Similarly, UNBS5162 could inhibit A549 non-small cell lung cancer cell proliferation by promoting apoptosis (11). In the present study, it was identified that 20 µM UNBS5162 exhibited a marked and similar inhibitory effect on, and low toxicity towards, SKOV3 ovarian cancer cells.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Shukla et al (26) reported a number of applications of apoptosis in prostate cancer. Similarly, UNBS5162 could inhibit A549 non-small cell lung cancer cell proliferation by promoting apoptosis (11). In the present study, it was identified that 20 µM UNBS5162 exhibited a marked and similar inhibitory effect on, and low toxicity towards, SKOV3 ovarian cancer cells.…”
Section: Discussionsupporting
confidence: 52%
“…UNBS3157 was designed to avoid the blood toxicity of the clinical metabolism amonafide (10). UNBS3157 is rapidly hydrolysed in physiological saline to produce UNBS5162 which exhibits anticancer activity (11). UNBS5162, a novel type of naphthalimide, was used to avoid the specific effects of the metabolite amonafide, including haemotoxicity (12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further research found that most metabolites and proteins on the purine metabolism, arginine and proline metabolism, and PI3K-Akt signaling pathway of A549 cells were down-regulated after treatment with TVN, which implied that TVN could inhibit the normal metabolism of A549 cells and slow down the proliferation rate of A549 cells. The PI3K-Akt signaling pathway is widely deregulated in the human tumor spectrum ( Liu et al, 2018 ). In addition, it promotes the cell cycle, cell proliferation, cell survival, and anti-apoptosis, which is achieved by activating Akt and downstream targets FOXO-1, GSK-3, etc.…”
Section: Resultsmentioning
confidence: 99%